(3caGjI GdCQjH aj eTGhQI GdWHjHs - (3SQj GdOjf CMeO Hf eMeO GdYdaj, GdTgjQ HGHf GdUGFZ,J (B991 (3g` s
(3ChdgG (B:s
(3jGef Mce Sjha GdYOe aj fMhQ GdehLhOGJ hMce , hbOe Hg bOe bOQg hbOQJg ai GdbOe hcGf Yde GdWH QCS GdYdhe hCSGSgG s
(3BNQgG (B:s
(3hGHJdGY NeS MHGJ ef MH GdCJQL Ydi GdQjb fGaY ef hLY GdXgQ hGdUdH hcPdc MHI GdNVQGA ebOGQ YTQjf MHI eSMhbI efNhdI, hMHI GdShOGA ai Pdc GdYdGL MSf s
(3Vef eLehY s
(3GfXQI eY OaY GdSehe Qbe (B"467"s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B207 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs